RETRACTED : Pengaruh strategi pembelajaran metakognitif preparing, doing, checking, dan assessing and following-up (PDCA) terhadap pengetahuan metakognitif dan prestasi belajar peserta didik kelas X MIPA SMAN 1 Turen pada materi larutan elektrolit dan non elektrolit - Binti Zulaihah; Parlan Parlan; Muhammad Su’aidy (Jurnal MIPA dan Pembelajarannya (JMIPAP), 2021)
Following a rigorous, carefully concerns and considered review of the article published in Jurnal MIPA dan Pembelajarannya (Journal of Mathematics, Science, and Instruction) to article entitle "Pengaruh strategi pembelajaran metakognitif preparing, doing, checking, dan assessing and following-up (PDCA) terhadap pengetahuan metakognitif dan prestasi belajar peserta didik kelas X MIPA SMAN 1 Turen pada materi larutan elektrolit dan non elektrolit" Vol. 1 No. 6 (2021). This paper has been found to be in violation of the Jurnal MIPA dan Pembelajarannya (Journal of Mathematics, Science, and Instruction) publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in ICOMSE The document and its content has been removed from Jurnal MIPA dan Pembelajarannya (Journal of Mathematics, Science, and Instruction) and reasnable effort should be made to remove all references to this article.